Pathological Complete Response to a Single Dose of Pembrolizumab‐Based Chemoimmunotherapy for Squamous Cell Carcinoma of the Lung: A Case Report - Yugo Matsumura; Seiya Ichihara; Kaori Nii; Kazumasa Nanjo; Naoki Kadota; Yoshio Okano; Hisanori Machida; Nobuo Hatakeyama; Hiroyuki Hino; Keishi Naruse; Tsutomu Shinohara; Shoji Sakiyama; et al. (Thoracic Cancer)
ABSTRACT We herein describe a patient with non‐small‐cell lung cancer who achieved pCR with a single dose of pembrolizumab‐based chemoimmunotherapy followed by surgery. A 61‐year‐old man was referred to our hospital with wheezing and an abnormal chest shadow. Squamous cell carcinoma of the left lower lobe, cT2aN1M0 stage IIB, was diagnosed and pembrolizumab‐based chemoimmunotherapy was initiated at the patient's request. One month later, chest CT revealed new ground‐glass opacities of the lungs, which were judged to be a CTCAE grade 2 pneumonitis due to an immune‐related adverse event (irAE). Therefore, steroid therapy was initiated. Prednisolone was tapered and discontinued as symptoms improved. A sleeve resection of the left lower lobe was performed, and a pathological complete response (pCR) was confirmed in a resected specimen. There has been no recurrence for 1 year and 7 months without treatment. This is the first case report of pCR to a single dose of chemoimmunotherapy followed by surgery for lung cancer. The present results suggest the potential of a single dose of chemoimmunotherapy to achieve pCR and cause irAEs in some patients.